Rapid-Slow Sand Filtration for Groundwater Treatment: Effect of Filtration Velocity and Initial Head Loss - Che Harun, Mohammad Hakim; Ahmad, Muhammad Irfan; Ali, Asmadi; Hamzah, Sofiah (International Journal of Integrated Engineering, 2022)
Iron (Fe) and manganese (Mn) are two of many substances that causing harm to human health and various environmental contamination. This study investigates the performance of rapid sand filter as an improvement to the existing commercial filter media. Rapid sand filters were tested using groundwater collected from Kg Budi Kelantan. Groundwater collected were tested using seven velocities ranging from 0.89 to 5.04ml/hr. The concentration of Mn, Fe and turbidity of the treated groundwater were compared. It is found that the highest Mn, Fe and turbidity removal were recorded by using velocity of 4.38ml/hr followed by 2.95ml/hr and 2.4 ml/hr. These three velocities represent more than 95% removal of final treated groundwater, where final Fe, Mn and turbidity ranging from 0.06 mg/L to 0.09 mg/L, 0 to 0.4 mg/L and 0.9 to 3.0 NTU, respectively. A positive trend also recorded where the initial head loss of the sand filter is directly proportional to the flow velocity. This means the filter media was still under a clean condition and no accumulation of sediment deposit occurs. The significance of this study to treat groundwater by removing the iron and manganese especially in rural areas were achieved successfully.